Cobalt oxide as a selective co-catalyst for water oxidation in the presence of an organic dye. Issue 12 (31st October 2017) - Kinastowska, K.; Barroso, J.; Yate, L.; Pavlov, V.; Chuvilin, A.; Bartkowiak, W.; Grzelczak, M.
Abstract : The use of Co3 O4 as co-catalyst improves selective water photo-oxidation to molecular oxygen in the presence of an organic dye. Abstract : In photobiocatalytical processes involving the simultaneous oxidation of water and reduction of specific organic molecules ( e.g., cofactors), the lack of physical separation of the redox half-reactions adversely affects the product stability. This is largely because organic molecules are generally less stable within harsh oxidative environments. In general, surface co-catalysts are able to improve the selectivity of photocatalysts towards water oxidation. However, harsh oxidative environments reduce the chemical stability of the organic molecules. Herein, we show that the use of Co3 O4 as a surface co-catalyst on silver orthophosphate improve water photo-oxidation in the presence of organic dye molecules, such as methylene blue, that typically exhibits susceptibility toward photodegradation. The presence of Co3 O4 on the photocatalyst surface prevents the adsorption of the organic dye, thus reducing its degradation rate. These findings provide a promising scenario for the visible light-driven reduction of organic molecules using water as an electron donor.